Trout-like multifunctional piezoelectric robotic fish and energy harvester. (23rd June 2021) - Tan, David; Wang, Yu-Cheng; Kohtanen, Eetu; Erturk, Alper
Abstract: This work presents our experimental studies on a trout-inspired multifunctional robotic fish as an underwater swimmer and energy harvester. Fiber-based flexible piezoelectric composites with interdigitated electrodes, specifically macro-fiber composite (MFC) structures, strike a balance between the deformation and actuation force capabilities to generate hydrodynamic propulsion without requiring additional mechanisms for motion amplification. A pair of MFC laminates bracketing a passive fin functions like artificial muscle when driven out of phase to expand and contract on each side to create bending. The trout-like robotic fish design explored in this work was tested for both unconstrained swimming in a quiescent water tank and under imposed flow in a water tunnel to estimate the maximum swimming speed, which exceeded 0.25 m s −1, i.e., 0.8 body lengths per second. Hydrodynamic thrust characterization was also performed in a quiescent water setting, revealing that the fin can easily produce tens of mN of thrust, similar to its biological counterpart for comparable swimming speeds. Overall, the prototype presented here generates thrust levels higher than other smart material-based concepts (such as soft polymeric material-based actuators which provide large deformation but low force), while offering simple design, geometric scalability, and silent operation unlike motor-based robotic fish (which often use bulky actuators and complex mechanisms). Additionally, energy harvesting experiments were performed to convert flow-induced vibrations in the wake of a cylindrical bluff body (for different diameters) in a water tunnel. The shed vortex frequency range for a set of bluff body diameters covered the first vibration mode of the tail, yielding an average electrical power of 120 μW at resonance for a flow speed around 0.3 m s −1 and a bluff body diameter of 28.6 mm. Such low-power electricity can find applications to power small sensors of the robotic fish in scenarios such as ecological monitoring, among others.